Human Resources (HR) Problems that Occur at PKBM Al Muttaqin - Gunawan, Caroline; Arif A, Muhammad; Sintiawati, Nani (Indonesian Journal of Adult and Community Education, 2023)
Problems faced by education in Indonesia in general include the quality of human resources, program quality, and program management. This problem in general often occurs in the scope of non-formal education in Indonesia, one of the programs is equality education which is considered to be even greater problematic in its implementation. The methodology in the research used is observational case study research in the sense that this research focuses on problems that are then understood and analyzed in depth with the group. The research method is used to describe holistically and comprehensively about the symptoms and events in the problem of equality education at PKBM AL MUTAQIN. The purpose of writing this scientific paper is to reveal the problems of human resources that occur in the implementation of equality education and how the efforts that can be offered by the group to overcome them, so that they can be used as guidelines for the future so that equality education can be better and independent. As for the results of the study, the first form of human resource problems is the lack of self-confidence and low motivation to follow learning, the second is the need for character strengthening for learning residents so that they do not want to be alone because of the assumption that they have more experience, third there is indecision and lack of appropriate variation in determining learning. The discussion of this study is the problems faced by equality education by looking at two sides of the main problem, namely problems from within the institution and problems from outside the institution. Another factor that is generally faced by institutions and programs is people who do not understand and understand the existence and importance of the role of non-formal education, especially equality education.